Analisis Manajemen Rantai Pasok Tanaman Anggrek Bulan di CV Bunga Alam Lestari Kota Semarang - Melayu, Alfiyo Anelza; Mukson, Mukson; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The study aims to analyze the supply chain management of Phalaenopsis orchids at CV Bunga Alam Lestari, as well as examine the structure of the network and business chain in the orchid supply chain. The research was conducted at CV Bunga Alam Lestari, located in Tambangan, Mijen, Semarang City, Central Java. A case study method was employed with purposive sampling, involving 20 respondents comprising producers, CV Bunga Alam Lestari, distributors, retailers, and consumers. Primary data were collected through observation and interviews, while secondary data were obtained from CV Bunga Alam Lestari. The analysis used descriptive quantitative methods, focusing on product, information, and financial flows, as well as supply chain management. The study applied the Supply Chain Operations Reference (SCOR) model, evaluating attributes such as reliability, responsiveness, flexibility, assets, and cost. The results indicate that the supply chain consists of six key actors: PT Eka Karya and Toko Anggrek Nambangan as producers, CV Bunga Alam Lestari, distributors, retailers, and consumers. The performance measurements for the supply chain show that responsiveness and flexibility reached the "superior" level, reliability achieved one "advantage" level measurement, while assets and cost also performed at the "advantage" level. The study concludes that improvements are needed in order fulfillment and cost management across all supply chain activities to minimize costs effectively.